Hydrokinetic Energy Opportunity for Rural Electrification in Nigeria - Ogunjuyigbe Ayodeji Samson Olatunji; Ayodele Temitope Raphael; Ibitoye Tahir Yomi (International Journal of Renewable Energy Development, 2018)
This paper is part of the ongoing research by the Power, Energy, Machine and Drive (PEMD) research group of the Electrical Engineering Department of the University of Ibadan. The paper presents various sites with possible hydrokinetic energy potential in Nigeria with the aim of quantifying their energy potential for rural electrification application. Overview of hydrokinetic technology is also presented with the view of highlighting the opportunities and the challenges of the technology for rural electrification. A case study of using hydrokinetic turbine technology in meeting the energy demand of a proposed civic center in a remote community is demonstrated.  Some of the key findings revealed that Nigeria has many untapped hydrokinetic potential site and if adequately harnessed can improve the energy poverty and boost economic activities especially in the isolated and remote rural communities, where adequate river water resource is available. The total estimated untapped hydrokinetic energy potential in Nigeria is 111.15MW with the Northern part of the country having 68.18MW while the Southern part has 42.97MW. The case study shows that harnessing hydrokinetic energy of potential site is promising for rural electrification. This paper is important as it will serve as an initial requirement for optimal investment in hydrokinetic power development in Nigeria.Article History: Received November 16th 2017; Received in revised form April 7th 2018; Accepted April 15th 2018; Available onlineHow to Cite This Article: Olatunji, O.A.S., Raphael, A.T. and Yomi, I.T. (2018) Hydrokinetic Energy Opportunity for Rural Electrification in Nigeria. Int. Journal of Renewable Energy Development, 7(2), 183-190.https://doi.org/10.14710/ijred.7.2.183-190